Design and implementation of a campus network architecture based on load-balanced vBRAS - FU Zhongnan; SHANG Qun; CHEN Junjun; LIU Wending (Tongxin xuebao)
In the context of the continuous expansion of university networks, the traditional BRAS (broadband remote access server) architecture faces numerous challenges in terms of user capacity, scalability, and operations management. A vBRAS architecture based on virtualization technology was proposed, aimed at addressing the shortcomings of the traditional BRAS in campus networks. By decoupling the control plane from the forwarding plane, vBRAS enabled efficient system scalability, flexible resource allocation, and centralized management. A detailed analysis of the design objectives, overall architecture, and the specific implementation of vBRAS in user access and session management processes was provided. After deploying the vBRAS architecture, Peking University's campus network has seen significant improvements in terms of capacity, operational efficiency, user experience, and resource utilization. In addition to supporting various backup mechanisms to ensure high availability, vBRAS also enhances user experience through seamless roaming. Overall, vBRAS offers an efficient, flexible, and cost-effective solution for the future development of university networks.